Mathematical Problem Solving Ability in Self-Directed Learning with Module From Students’ Self-Regulated Learning - Amaliyah, Fitriyah; Sukestiyarno, YL; Asikin, Mohammad (Universitas Negeri Semarang, 2021)
This study aims to describe students’ mathematical problem solving ability from students’ self-regulated learning in self-directed learning with module. The method used in this research is mixed methods research with a sequential explanatory design. The population in this research are all 11th grade students at SMA N 1 Mayong. The sampling technique from self-regulated learning has taken 7 subjects used purposive sampling. The result showed that students with high self-regulated learning categories are able to achieve three indicators of problem solving abilities namely understanding problems, making problem solving strategy plans and implementing problem solving strategy plans correctly. Students with moderate self-regulated learning categories are able to achieve two indicators of problem solving abilities namely understanding problems and making problem solving strategy plans correctly. While students’ low self-regulated learning categories have not been able to achieve all four indicators of problem solving abilities namely understanding problems, making problem solving strategy plans, implementing problem solving strategy plans and looking back.